Nanoencapsulamento do bioativo acetil hexapeptídeo com biopolímero têxtil para aplicação dermocosmética - Freire, Aline Gabriel (2019)
The use of biopolymers derived from textile fibers in nanostructured complexes for administration and controlled release of drugs has been emerging in several areas of biotechnology. In the cosmetic area, the use of nanoparticles as encapsulating agent of active molecules has the advantage of protection against oxidation, photolysis and hydrolysis, better skin permeation, increased shelf life, controlled release, reduction of skin irritation, improvement of bioavailability, targeting of the drug to the dermis, among other factors. In this sense, fibroin extracted from silk fiber, is a promising biopolymer for application in health and cosmetics due to its characteristics of biocompatibility, biodegradability, non-toxicity and microbial resistance. In this context, the acetyl hexapeptide biopolymer, commercially known as Argireline®, is a synthetic macromolecule developed to mimic botulinum toxin in the reduction of wrinkles and expression lines. This substance has a high molecular weight and has a hydrophilic characteristic, which hampers the permeation to the deeper layers of the skin, agglomerating only on the surface of the stratum corneum. The objective of this work was to develop acetyl hexapeptide nanoparticles using silk fibroin as a polymer matrix for potential application in topical dermocosmetic formulations that allow the controlled release of the drug in a deep layer of the skin and to evaluate in vitro cytotoxicity using fibroblasts from the L929 strain. The nanoparticles were prepared by the desolvation method at different concentrations. The nanoparticles were analyzed for their morphology, size, surface charge, encapsulation efficiency, active release and cytotoxicity. The following equipment was used: dynamic light scattering (DLS), zeta potential, scanning electron microscopy with field effect (SEM-FEG), molecular absorption spectroscopy in the ultraviolet and visible (UV-Vis) region, Fourier transform infrared spectroscopy (FTIR), analysis thermogravimetric (TG), cell viability and in vitro controlled release. The obtained nanoparticles had diameters between 70 and 150 nm, with spherical morphology. FTIR results demonstrated the presence of the drug in the nanosystem. In the release profile, a 6% release of the bioactive was observed after 1h and 30 minutes of assay and after 24h, it presented a 28% release at pH 5.5. At neutral pH, there was a 43% bioactive release after 24h. The nanoparticles with acetyl hexapeptide did not present cytotoxicity at concentrations of 0.1 mg/mL and 0.05 mg/mL, making application to the epithelial tissue viable.